The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.21608/adjg.2018.17187
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chinese Green Tea on Enamel Surface Characteristics in an in-vitro Erosion Model

Abstract: Objectives: Erosive tooth wear is a common worldwide problem. It manifests due to consumption of high caloric and low pH acidic drinks such as carbonated soft drinks and fruit juices, which cause irreversible damage to dental hard tissues. The aim of this study was to evaluate the effect of Chinese green tea on surface characteristics of eroded enamel in an in-vitro erosion model. Materials and methods: Twenty sound extracted human premolars were selected. Micro-hardness and surface roughness were measured bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
2
4
0
1
Order By: Relevance
“…Green tea with both concentrations confirmed the highest remineralizing effect on initial demineralized enamel which were in agreement with Aidaros et al and Talaat with no harmful effect on enamel (14) . The results was also supported by S. Amal et al study who concluded that green tea was the highest remineralizing efficacy than 0.05% sodium fluoride (33) .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Green tea with both concentrations confirmed the highest remineralizing effect on initial demineralized enamel which were in agreement with Aidaros et al and Talaat with no harmful effect on enamel (14) . The results was also supported by S. Amal et al study who concluded that green tea was the highest remineralizing efficacy than 0.05% sodium fluoride (33) .…”
Section: Discussionsupporting
confidence: 90%
“…Other studies have also demonstrated the inhibition of salivary amylase activity that may contribute significantly to reducing the cariogenicity of starch-containing foods by extracts of a commercial tea (17) . Green tea contains high fluoride content (17,30) and also high pH value which is about 6.3 (14) that may be the reason of being a remineralizing agent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Green tea is a leading drink in the Far East for thousands of years before it became a popular hot and cold drink worldwide. Many studies have suggested that the consumption of green tea is associated with the reduction of the risk of several pathologies and an increasing number of evidences mentioning a beneficial role of green tea in oral health [9].…”
Section: Introductionmentioning
confidence: 99%